The Saddle-Shaped Thoughts Transformation of Mao Zedong in the Agrarian Reforms of China - Sun, Ping (Advances in Social Sciences Research Journal, 2019)
The thoughts transformation of Mao Zedong in the land ownership policies can be divided into three stages and was saddle-shaped. First, the traditional Chinese Great Harmony, his life-long guiding principle upon the various policies, decided his preference for the public land ownership when he was still young. Secondly, as a pragmatist, Mao transformed his thought to adopt private ownership policy for more than twenty years (1930-1953). Thirdly, when Mao Zedong possessed the authority over the country, he released the general line, started the Great Leap Forward, and proposed the People’s Communes to realize his idealized target, a purer communist country, which resulted in a great disaster. The whole process of Mao Zedong’s thoughts transformation was a result of his compromise between the ideal in his mind and the reality of the society.